Biology and management of two Hordeum weedy species: A review. (November 2019) - Iqbal, Nadeem; Bajwa, Ali Ahsan; Manalil, Sudheesh; Khan, Asad Muhammad; Kebaso, Lynda; Frimpong, David; Ali, Hafiz Haider; Jha, Prashant; Chauhan, Bhagirath Singh
Abstract: Hordeum murinum subsp. leporinum (Link) Arcang. (Syn. Hordeum leporinum ) and Hordeum murinum subsp. glaucum (Steud.) Tzvelev. (Syn. Hordeum glaucum ) are recognized as problematic weeds across all continents. Both these weedy species have similar morphological features, but they can be distinguished by their ploidy levels, climate adaptability and differences in spikelets and floral structure. These weedy species have now become a serious threat to agricultural productivity and have evolved as invasive weeds due to their genetic diversity and biological, physiological and ecological adaptations. Several biological characteristics like seed dormancy, the enclosed barbed awns, rapid germination and growth rate, and early maturation have made these two weedy species highly invasive and adaptable to Mediterranean type climates. These weedy species pose a serious threat to animal productivity as well. The presence of long awn on the spikelets at the flowering time can cause severe production losses, owing to sheep deaths. These weeds also serve as alternate hosts for insects and pathogens in different crops and pastures. The evolution of herbicide resistance against the main sites of action viz. acetolactate synthase (ALS) inhibitors, acetyl co-enzyme A carboxylase (ACCase) inhibitors, and photosystem I (PS I) inhibitors have made these weedy species more problematic for the farming community. A detailed investigation of the biology, ecology, herbicide resistance mechanisms and management of these weedy species is essential to understand their population dynamics under different management scenarios and develop integrated, multi-tactic strategies to prevent further development and spread of resistance of these weeds. Highlights: Hordeum leporinum and H. glaucum are ubiquitous weeds of dry and temperate regions. Both weedy species can survive and reproduce under adverse climatic conditions. Both weedy species have evolved resistance against three major herbicide groups. Dormancy evolution to delayed emergence plus HR biotypes makes them problematic. Both weedy species are arduous to control with the current weed control measures.